The Influence of Supervisory Roles and Distribution Duties on Community Satisfaction Recipients of Self-Help Housing Stimulant Assistance (BSPS) - Suriyanti R.; Nusraningrum, Dewi (PT Inovasi Pratama Internasional, 2024)
The implementation of housing policy in the form of Self-Help Housing Stimulant Assistance (BSPS) in Indonesia is still not fully in line with expectations. The aim of this research is to analyze the effect of supervision and distribution on the satisfaction of people receiving the BSPS program in Cakura Village. The method used in this research is multiple linear regression with the Ordinary Least Square (OLS) estimation technique. The results of the research conclude that there is a positive influence from supervision (X1) on the level of satisfaction of the community receiving the program (Y) in Cakura Village. However, this influence is very small and not significant, with a correlation coefficient value of 0.343 and a significance level of 0.206. There is a positive influence from distribution (X2) on the satisfaction of program recipients (Y) in Cakura Village. Like the influence of the PPK supervisory role, the influence of the TFL distribution task is also very low as indicated by the correlation coefficient value of 0.477 and the significance level of 0.035. There is an influence of supervision and distribution together on community satisfaction with a coefficient of determination value of 0.578. This means that changes that occur in variable Y (community satisfaction) can be determined by changes that occur in variables X1 (supervision) and X2 (distribution) amounting to 57.8%. Meanwhile, the remainder, amounting to 0.422 or 42.7% of the change in variable Y is determined by other variables that are not included in the regression equation model.